First fossil record of an East Asian endemic genus Sladenia (Sladeniaceae) from its modern range: Implications for floristic evolution and conservation biology. Issue 1 (31st July 2019) - Jia, Lin‐Bo; Manchester, Steven R.; Huang, Jian; Su, Tao; Xue, Li; Zhang, Shi‐Tao; Huang, Yong‐Jiang; Zhou, Zhe‐Kun
Abstract: Fossil records of endemic plants play an important role in recognizing the floristic history of East Asia and thereby facilitate the conservation of plant diversity in the region. However, the fossil record of many extant East Asian endemic genera remains poorly documented thus far. Here, we report an infructescence fossil of an East Asian endemic genus, Sladenia (Sladeniaceae), from the early Miocene of southeastern Yunnan, China. The fossil is characterized by: (i) dichasial cymes; and (ii) flask‐shaped ovary with dense subparallel ribs on the surface extending from the base to the distal end of the united style. It represents the first fossil record of Sladenia in Asia, showing that the genus was established in the region at least by the early Miocene. Given that a much older fossil record of Sladeniaceae has been reported from Africa and the sister group of Sladenia is distributed only in Africa, Sladenia is not likely of East Asian origin. The present endemic status of Sladenia was possibly achieved by regional extirpation in Africa and taking refuge in East Asia. This case thus supports the "Museum" rather than "Cradle" hypothesis for the genesis of high plant species in the flora of East Asia. A comparison of the present fossil with extant Sladenia infructescence shows morphological stasis from the early Miocene to present. Such evolutionary tardiness might have resulted in the reduced fitness of the genus, which further caused its current endangered situation.